Accuracy of Triage and Its Association with Family Satisfaction in the Emergency Department of a General Hospital: A Cross-Sectional Study - Delianto; Kumar, K. Sesha (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Triage is a critical process in emergency departments (EDs), determining patient prioritization based on condition severity. While triage accuracy is crucial for clinical outcomes, its influence on family satisfaction remains underexplored, particularly in rural Indonesian settings. This study aimed to examine the relationship between triage accuracy and family satisfaction in the emergency department of Mokoyurli General Hospital, Buol Regency. Methods: A cross-sectional design was used involving 113 family members of ED patients selected through accidental sampling. Triage accuracy was assessed based on standard criteria (red, yellow, green), while family satisfaction was measured using a validated questionnaire covering six domains. Data were analyzed using descriptive statistics and Spearman’s rho correlation Result: Among the respondents, 77% experienced accurate triage, while 23% did not. In terms of satisfaction, 18.6% were dissatisfied, 44.2% fairly satisfied, and 37.2% satisfied. A strong, statistically significant correlation was found between triage accuracy and family satisfaction (ρ = 0.710, p < 0.001). Respondents particularly appreciated timely communication and respectful care, although moderate satisfaction remained predominant. Conclusion: Triage accuracy significantly influences family satisfaction, functioning as both a clinical and emotional reassurance mechanism. Enhancing emergency nurses’ triage competencies and interpersonal communication can improve care experiences. Hospitals, especially in rural areas, should integrate structured triage protocols with clear communication strategies to build trust and satisfaction. Future research should include mixed-method approaches to capture nuanced family perspectives and assess long-term satisfaction trends.